Minimal clinically important improvement/difference (MCII/MCID) and patient acceptable symptom state (PASS): what do these concepts mean?. (12th October 2007) - Kvien, Tore K; Heiberg, Turid; Hagen, Kåre B
Abstract : An increasing focus has over recent years been directed to the use of categorical endpoints to define response, i.e. to define cut-points for important improvement and/or acceptable clinical state. The levels of Minimal Clinically Important Improvement (MCII) are typically defined according to the patients perception of what is an important improvement. It can be defined as the smallest change in measurement that signifies an important improvement. MCII signifies an improvement of relevance in a clinical trial, or the minimal meaningful change at an individual level. The Minimal Clinically Important Difference (MCID) may reflect either an improvement or a worsening. Patient Acceptable Symptom State (PASS) has been defined as the highest level of symptom beyond which patients consider themselves well. Cut-points for MCII and PASS are usually identified through two different statistical approaches. The 75th percentage approach identifies the cut-point corresponding to the 75 percentile of the scores for improvement in patients who report an important improvement by the anchoring question. Applying receiver operating characteristic (ROC) curves allows for choosing the threshold that is the best compromise between sensitivity and specificity for each outcome criterion. The identified cut-points for MCII and PASS may easily be incorporated as endpoints in clinical trials, and will provide information about the proportion of patients that achieve an improvement exceeding the level accepted as MCII and achieve a state accepted as PASS.